Assessing student writing: EFL teachers’ actual practices and the effects of using the Composition Profile : - Nguyễn, Thị Mộng Tuyền (Trường Đại học Cần Thơ, 2015)
Investigated how EFL teachers actually assessed studnet wrting and the extent to which the ESL composition profile aides EFL teachers in assessing student writing